Influence of Novelty Centered Business Model Innovations on the Performance of Manufacturing Firms in Kenya - Maundu, Michael; Makau, Godfrey; Wekesa, Susan (International Journal of Scientific Research and Management (IJSRM), 2024)
Strategic management scholars agree that innovation in business models is essential for long-term survival in challenging commercial environments. The study was designed to determine the influence of novelty centered business model innovation on the Kenyan manufacturing companies’ performance. The study was anchored on diffusion of innovation theory. The study adopted the descriptive research design and positivism philosophy that was aligned to the classical scientific method of research inquiry. Multi-stage sampling method was adopted to collect data from top management team in the manufacturing sector using a semi- structured questionnaire. The data was analysed using descriptive analysis techniques such as mean, percentages and standard deviation.  The study established that novelty centered business model innovation positively and significantly influenced manufacturing firms’ performance.  The study recommends that manufacturers should endeavour to innovate their business models in order to achieve superior long-term performance. The study findings inform the extent to which  novelty centered business model innovation predicts the performance of manufacturing firms.